San Jose Civic Auditorium interior - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the interior of the San Jose Civic Auditorium from the perspective of the stage. The auditorium is filled with spectators. A piano and a microphone stand on the stage.